Permainan Roda Pelangi Untuk Penerapan Nilai 4B (Baiman, Bauntung, Batuah, Dan Baadab) Pada Siswa Kelas VIII SMP Negeri 6 Banjarmasin - Prilia, Dinda; Sulistyana, Sulistyana; Sugianto, Akhmad (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
This study aims to describe the application of 4B values ​​(Baiman, Bauntung, Batuah, and Baadab) to class VIII students at SMP Negeri 6 Banjarmasin before group guidance with the rainbow wheel game was carried out, after the service was carried out, and to analyze the effectiveness of group guidance services with the rainbow wheel game. for the application of 4B values ​​(Baiman, Bauntung, Batuah, and Baadab). The research method used is an experiment with a pretest-posttest control group design. A sample of 8 students was divided into 2 groups, namely the control group and the group treatment. The data collection instrument used the 4B implementation scale and the Rainbow Wheel game scale. Sampling technique using purposive sampling. Data analysis used the T-count formula. The results of the analysis showed that T-hi>T-tab was 3.92 > 1.94 which means The Rainbow Wheel game in group guidance services is effective for the application of 4B values ​​(Baiman, Bauntung, Batuah, and Baadab) to students.